De la nation à la région, l’Histoire de l’art, archéologie et mythes fondateurs - Allios, Dominique (Hortus Artium Medievalium, 2014)
Abstract From the XIX century, History becomes a political tool in the nationalists political movements. Archaeology and History of Art used to justify the founding myths, because of their history subservient to statutes and serving as scientific « evidence». Any time, all territorial expansion policies seek legitimacy by appealing to the historical argument and that all political and religious orientations and sensitivities combined. The debate is old, but the means and applications usually belong to the same process, even though the uses and motivations can be extremely varied. But it is in France, from the July Monarchy and 1830s, that history is the foundation and reference for the government and the nation. Periods are preferred, making a consensus among historians, archaeologists, writers and politicians. Among them the Middle Ages to the July Monarchy, the Gallic revolt for the empire of Napoleon III, the Hundred Years War and his heroine Joan of Arc after the defeat of Sedan in 1870, or the victory of the first World War which are all best-known and most famous examples. It is interesting to note that contemporary conflicts are mainly based on territorial claims whose justifications are political, racial , ethnic, religious , but consistently show an argument whose schema and operating procedures are identical , whatever the nature the conflict. Instead of archeology and history of art is not neutral and is often used as evidence as we have seen during the Second World War and even today. Archaeologists, or at least their research, are either deliberately set or retrieved either unwittingly apology to such claims.